THE INFLUENCE OF LEARNING OUTCOMES STYLE DURING THE COVID- 19 PANDEMIC - Martoyo Martoyo; Muhamad Uyun; Muhammad Isnaini; Halen Dwistia; Ari Nuraini (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This research is motivated by the problem of the lack of students who are aware of their own learning style, when the learning process students find it difficult to accept the material taught by the teacher. This type of research is quantitative which is descriptive associative. The population of this study was all 35 students in grade VIII PKBM SabilulBelievers . As for the research sample researcher uses a total sampling that all individuals are chosen as sample members. The results of research in this thesis are indicating that the influence of learning styles on learning outcomes of Aqeedah Morals Class VIII Pandemic Covid-19 Academic Year 2020/2021. The Effect of Learning Style has a positive and significant influence on the learning outcomes of the Aqeedah Moral Class VIII Subjects in Pandemic Covid-19 at PKBM SabilulMukminin with a significant level of 5%, seen from the value of X 2 count 20.594 > x 2 9.488 and the coefficient of coatual /level of 0.608, which shows a strong effect.